2023
DOI: 10.1186/s12888-023-04965-9
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal blood lipid and electrocardiogram characteristics in common mental disorders

Abstract: Background At present, there is not enough evidence to prove the relationship between blood lipid and electrocardiogram (ECG) abnormalities in common mental disorders (CMD). This study aimed to explore the relationship between them, to detect and prevent arrhythmia or sudden death. Methods We collected 272 CMD patients (maintained a fixed drug dose pattern for 1 year or more), including 95 schizophrenias (SC), 90 bipolar disorders (BD) and 87 major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In our study, all sugars/lipids/BP were associated with heart rate except LDL-C. An increase in these traits was associated with an increase in heart rate, except for HDL-C, which was negatively correlated with heart rate. In a recent study with a relatively small sample size, a positive correlation was observed between heart rate and HDL-C, LDL-C, BMI, and TG [ 29 ]. Our results should be more accurate because of our larger sample size (40× higher) and thus higher statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all sugars/lipids/BP were associated with heart rate except LDL-C. An increase in these traits was associated with an increase in heart rate, except for HDL-C, which was negatively correlated with heart rate. In a recent study with a relatively small sample size, a positive correlation was observed between heart rate and HDL-C, LDL-C, BMI, and TG [ 29 ]. Our results should be more accurate because of our larger sample size (40× higher) and thus higher statistical power.…”
Section: Discussionmentioning
confidence: 99%